Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting